DEVELOPMENT OF AN INTERNAL AUDITORS' WHISTLEBLOWING MODEL AT REGIONAL INSPECTORATES ACROSS THE PROVINCE OF BANGKA BELITUNG ISLANDS, WITH SOCIAL INFLUENCE AS A MODERATOR - Erwandy, Erwandy; Aris Setyanto Nugroho; Harnovinsah, Harnovinsah; Darmansyah, Darmansyah (International Journal of Social Science, 2025)
This study aims to develop an effective whistleblowing model for internal auditors at regional inspectorates across the Province of Bangka Belitung Islands. The development of the whistleblowing model is based on the Theory of Planned Behavior, with social influence serving as a moderating variable. Social influence is measured through the dimensions of conformity, compliance, and obedience. The study involved 227 auditors and Regional Government Administration Supervisors (P2UD). Data were collected using Google Forms and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the hypothesized relationships between variables. The results show that attitude towards behavior has a positive and significant effect on whistleblowing intention. Subjective norms also have a positive and significant effect on whistleblowing intention, as does perceived behavioral control. Whistleblowing intention has a positive and significant effect on whistleblowing behavior. Whistleblowing intention mediates the effects of attitude towards behavior, subjective norms, and perceived behavioral control on whistleblowing behavior. The dimensions of conformity, compliance, and obedience significantly manifest the construct of social influence. Social influence has a direct positive and significant effect on whistleblowing behavior. However, social influence does not significantly moderate the effect of whistleblowing intention on whistleblowing behavior.